Plant breeding reviews. Volume 36 - Janick, Jules , 1931- (Hoboken, New Jersey : Wiley Blackwell, 2012)
Plant Breeding Reviews presents state-of-the-art reviews on plant breeding and genetics covering horticultural, agronomic and forestry crops, incorporating both traditional and molecular methods. The contributions are authored by world authorities, anonymously reviewed, and edited by Professor Jules Janick of Purdue University, USA. The series is an indispensible resource for crop breeders, plant scientists, and teachers involved in crop improvement and genetic resources
1. Dedication: Rodomiro Ortiz plant breeder, catalyst for agricultural development -- 2. Phenotyping, genetic dissection, and breeding for drought and heat tolerance in common wheat: status and prospects -- 3. Nutritionally enhanced staple food crops -- 4. Genetic management of virus diseases in peanut -- 5. Common bean breeding in the tropics -- 6. New approaches to cassava breeding
Sponsored by the American Society for Horticultural Science, et al.
Includes bibliographical references and index
Keywords: Plant breeding; Plant propagation